Amino Acid Transport by the Filamentous Fungus Arthrobotrys conoides - Gupta, Rishab K. (1970)
Uptake of l-valine by germinated spores of Arthrobotrys conoides has all the characteristics of a system of transport that requires an expenditure of energy by the cells. It is dependent on temperature and has an energy of activation of 16,000 cal/mole. Uptake is optimal at pH 5 to 6. l-Valine accumulated against a concentration gradient and is not lost from the cells by leakage or exchange. The process requires energy supplied by the metabolic reactions that are inhibited by catalytic amounts of 2,4-dinitrophenol and azide. The kinetics of the system are consistent with a mechanism of transport that depends on a limited number of sites on the cell surface, and the Michaelis constant for the system is 1.5 × 10(−5) to 7.5 × 10(−5)m. Modification of the amino or carboxyl group abolishes l-valine uptake. The process is competitively inhibited by d-valine, glycine, and other neutral amino acids (K(i) = 1.5 × 10(−5) to 4.0 × 10(−5)m), indicating a lack of stereospecificity, and also indicating that aliphatic side chain is not required for binding with the carrier. The transport system has less affinity for acidic amino acids (glutamic and aspartic acids) than neutral amino acids, and a greater affinity for basic amino acids (histidine, lysine, and arginine). The range of affinity is in the order of 100, as measured in terms of K(i) values for various compounds. The data presented provide suggestive evidence that the uptake by A. conoides of all amino acids except proline is mediated by a single carrier system that possesses an overall negative charge.